2011
DOI: 10.3923/jest.2011.139.149
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Occurrence and Seasonal Distribution of Antibiotic Resistance Heterotrophic Bacteria and Physico-chemical Characteristics of Muthupettai Mangrove Environment, Southeast Coast of India

Abstract: A study on antibiotic resistance of heterotrophic bacteria and physicochemical characteristics of water and sediment in mangrove environment of Muthupettai, Southeast coast of India was carried out during April 2006 -March 2007. Six stations in and around the mangrove sites were selected for sampling and the following parameters were recorded at monthly intervals temperature, pH, salinity, dissolved oxygen, nitrite, nitrate, total nitrogen, inorganic phosphate, total phosphorus, ammonia, silicate and total org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
3
7
0
Order By: Relevance
“…Humans and animals have been reported as sources of antibiotic-resistant organisms in water environments and can transfer antibiotic resistance genes to other pathogens and naturally occurring water microbes through transposons, plasmids and integrons [ 47 , 48 ]. Bacteria isolated from beach sand, seawater and sediments have recorded resistance to various antimicrobials [ 48 , 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Humans and animals have been reported as sources of antibiotic-resistant organisms in water environments and can transfer antibiotic resistance genes to other pathogens and naturally occurring water microbes through transposons, plasmids and integrons [ 47 , 48 ]. Bacteria isolated from beach sand, seawater and sediments have recorded resistance to various antimicrobials [ 48 , 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resistance of bacteria occurring in marine ecosystems to different antibiotics was recorded in seawater, sediments and beach sand (Schwartz et al 2003, Mudryk 2005, Mudryk et al 2010, Oliveira et al 2010, Manivasagan et al 2011. The rapid increase in the number of resistant and multiresistant aquatic bacteria is partly due to their ability to transfer antibiotic resistance agents (plasmids, transposons and integrons) among bacterial populations by cell to cell contact (Oliveira et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive responses of bacterial communities to several antibiotics documented in the present study may have some potential implications for the public health (Ramesh et al 2010). According to Manivasagan et al (2011), the difference in the percentage of bacteria resistant to various antibiotics may reflect the history of antibiotics' application and hence may serve as an indicator. Reinthaler et al (2003) and Mudryk (2005) showed that bacterial resistance to antibiotics depended on their chemical structure; the results of the present study also support this finding.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…The metal accumulating (Cu, Cd, Ni, Vd) property of some marine bacteria make them potential sources for bioremediation (De et al, 2006;Miranda and Rojas, 2006). Bacterial isolates from marine waters demonstrated varying degrees of resistance to antibiotics like Chloramphenicol, ampicillin, streptomycin, tetracycline and kanamycin (Manivasagan et al, 2011;Souza et al, 2006). Certain bacterial isolates from marine coast of West Bengal have already been isolated and characterized.…”
Section: Introductionmentioning
confidence: 99%